Risk Factors for Residual Stenosis After Carotid Artery Stenting - Tao, Yunlu; Hua, Yang; Jia, Lingyun; Jiao, Liqun; Liu, Beibei (Frontiers in Neurology, 2021)
Background and purpose: Stent residual stenosis is an independent risk factor for restenosis after stenting. This study aimed to analyze the factors influencing residual stenosis after carotid artery stenting (CAS). Methods: A total of 570 patients who underwent CAS with 159 closed-loop stents (CLS) and 411 open-loop stents (OLS) from January 2013 to January 2016 were retrospectively enrolled in this study. Carotid stenosis location in the common carotid artery or in internal carotid artery, plaque size and features (regular or irregular morphology; with or without calcification), degree of carotid artery stenosis, and stent expansion rate were detected by carotid duplex ultrasonography. Residual stenosis was defined as a stenosis rate ≥30% after CAS, as detected by digital subtraction angiography. A logistic regression analysis was used to analyze residual stenosis risk factors. Results The overall incidence of residual stenosis was 22.8% (130/570 stents). The incidence of residual stenosis in the CLS group was higher than that in the OLS group (29.5% vs. 20.2%, χ2 =5.71, P=0.017). The logistic regression analysis showed that CLS (odds ratio, OR 1.933; 95% CI, 1.009-3.702), irregular plaques (OR 4.237; 95% CI 2.391-7.742), and plaques with calcification (OR 2.370; 95% CI, 1.337-4.199) were independent risk factors for residual stenosis after CAS. And a high radial expansion rate of stent was a protective factor for residual stenosis (OR 0.171; 95% CI, 0.123-0.238). The stenosis location and stent length did not impact the occurrence of residual stenosis. After one-year follow-up, the incidence of restenosis in the residual stenosis group was higher than that in the group without residual stenosis (13.1% vs.2.0%, χ2 =28.05, P<0.001). Conclusions: The findings of this study suggest that plaque morphology, echo characteristics (with calcification), and stents type influence residual stenosis.